Sources of risk in construction project development / Noor Hafizah Mohd Noor - Mohd Noor, Noor Hafizah (2007)
The main objective of report is to determine which risks are likely to affect a construction project development, comprise fundamental step in project risk management processes such as explained in the literature review. The potential risk sources should be identified at the early stage of a project development; it could avoid pitfalls by eliminating or minimizing the cause of the adverse events. This report presents the results of study aimed at identifying and categorizing risk elements in construction project development, and exploring strategies for eliminating or minimizing the identified risk sources. Results show that sources of risks in construction project development could be categorized into controllable (mainly due to acts or omissions of internal stakeholders - client, consultants, main- and sub-contractors, and suppliers) and uncontrollable sources (macro and micro economics and global dynamics, legislative / statutory / political controls, force majeure and environmental constraints). Potential risk elements under each source are identified and prioritized in relation to their levels of impact. Effective strategies for efficient risk identification development are also identified.